2021
DOI: 10.1016/j.ajogmf.2020.100269
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department use among postpartum women with mental health disorders

Abstract: Background Mental health disorders (MHD) are becoming more recognized in pregnancy. Whether MHD are associated with health services utilization postpartum is incompletely understood. Objective To investigate postpartum emergency department (ED) use within 30 days of delivery among women with preexisting MHD during pregnancy. Study Design This was a retrospective cohort study evaluating ED use among postpartum women with or without MHD who del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…PNA has also been suggested as a risk factor for paternal anxiety and depression in the perinatal period ( 29 , 30 ). It has also been reported that women with PNA may struggle to identify appropriate ways to seek medical support, and may access emergency medical care at a greater frequency than those without PNA ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…PNA has also been suggested as a risk factor for paternal anxiety and depression in the perinatal period ( 29 , 30 ). It has also been reported that women with PNA may struggle to identify appropriate ways to seek medical support, and may access emergency medical care at a greater frequency than those without PNA ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Point prevalence of minor depression has been shown to be as high as 11-18% in pregnancy and 13-30% postpartum 20,63,65 . Prevalence estimates of other psychiatric diagnoses in the perinatal period include a prevalence of 11-21% for anxiety disorders, 2.8% for bipolar disorder, and 0.1-1% for psychotic disorders, with many more women likely experiencing subthreshold symptomatology [21][22][23]63,66 . The highest risk period for postpartum depression has been suggested to be the first 9 months postpartum 22 .…”
Section: Maternal Mental Illness 221 Definitions and Epidemiology Of ...mentioning
confidence: 99%
“…Prior research has suggested that approximately 0.2%-4.2% of women present to the emergency department for mental health concerns in the postpartum period 66,80,81 . A large retrospective population-based study in Ontario, Canada found that 1.1% of women visited the emergency department for a mental health concern in the first postpartum year, with a median time to index presentation of approximately 5 months, and in 60% of cases, the ED represented the first postpartum point of access for mental health care 80 .…”
Section: Severe Maternal Mental Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The predictors of ED visits are similar to those of patients who do not attend their clinic appointments: public insurance, younger age, cesarean delivery, and antepartum complications, 13 specifically mental health disorders. 14 If patients are not attending their clinic appointments, one could hypothesize that they may visit the ED for their routine postpartum care instead. The objective of our project was to determine whether shortening the time to initial postpartum visit from 6 weeks to 2 weeks can increase postpartum visit attendance of patients and decrease the rate of ED visits within 30 days after delivery.…”
Section: Introductionmentioning
confidence: 99%